3: The Prevalence of Normocephalic Sagittal Craniosynostosis in Young Children. (July 2021) - McGrath, Jennifer L.; Manrique, Monica; Mantilla-Rivas, Esperanza; Rana, Md Sohel; Crowder, Hannah; Ichiuji, Brynne; Aivaz, Marudeen; Oh, Nathanael; Oh, Albert K.; Rogers, Gary F.
Abstract : Purpose: Sagittal craniosynostosis (SC) is usually diagnosed during early childhood due to the presence of an abnormal head shape termed scaphocephaly. However, patients with radiographic evidence of a prematurely fused sagittal suture but normal head shape (normocephalic) have been reported. A recent study from our group found that 3.3% of normal children under 5 years of age have partially or completely fused sagittal sutures by computed tomography but no corresponding changes in cranial form. The purpose of this paper is to validate our preliminary study with a larger cohort of patients, and to analyze factors that may be associated with incidental finding of early suture fusion. Methods: We reviewed computerized tomography (CT) scans of patients from 0 to 71 months of age who presented to the emergency department (ED) of our tertiary care institution between 2008 and 2020. Patients who were found to have syndromes related with craniosynostosis, phenotypes consistent with craniosynostosis, VP shunt placement, brain or cranial abnormalities, were excluded. A panel of two craniofacial surgeons reviewed the CT scans for presence of craniosynostosis (CS). Demographic information, gestational age, past medical and family history, medications, chief complaint and fusion type were recorded as covariates. Possible medical or demographic differences between patients with and without craniosynostosis were analyzed using unpaired t-test and Chi-square/Fisher's exact test; Firth logistic regression was performed to determine the association between the independent covariates and the presence of CS in two sub-cohorts; patients ⩽ 24 months of age and patients over 24 months of age. Results: We identified 870 patients with a mean age of 30.1 months. 41 patients (4.71%) had fusion the sagittal suture (25 complete, 16 incomplete); all patients had a normal cranial index (width/length >0.7). The prevalence increased from 0-24 months, then was constant from 25-71 months. In the affected patients under two years of age, those with family history of neurodevelopmental disease had 49.32 (95% CI [4.28, 567.2]) times higher odds of developing CS. Sub-cohort encompassing patients above 24 months of age showed no variable as independent predictor for developing CS. Conclusion: Normocephalic SC in young children is common. While the impact of this condition is unknown, the correlation with family history of neurodevelopmental disease is concerning.